Orbital apex syndrome with frontal abscess secondary to sinusitis due to Candida guilliermondii - Abd Bari, Muhd. Syafi; Ab Kahar, Mas Edi; Nordin, Hudzaifah; Salim, Rosdan; Idris, Zamzuri; Wan Hitam, Wan Hazabbah; Ismail, Shatriah (Kugler Publications, 2021)
Candida guilliermondii is an opportunistic pathogen that rarely causes invasive candidiasis even in immunocompromised humans. We report a case presenta-tion of invasive C. guilliermondii rhinosinusitis causing an orbital and intracranial extension (frontal lobe abscess). An aggressive multidisciplinary team management is a key approach in invasive fungal sinusitis and avoided mortality in this case. When orbital apex syndrome secondary to sinusitis is encountered in an immuno-compromised patient, the treating physician should consider fungal infection as a causative agent.